Narasi Kebencian dan Krisis Etika Komunikasi di Media Sosial: Analisis Wacana Dakwah di Tengah Disinformasi Digital - Abd. Kholiq; Sutikno (Program Studi Komunikasi dan Penyiaran Islam (KPI) Institut Agama Islam Tarbiyatut Tholabah (IAI TABAH), 2025)
The phenomenon of hate speech narratives on social media reflects an increasingly complex crisis in communication ethics in the digital disinformation era. Dakwah, which should be a means of moral education, is now often trapped in polarizing rhetoric that narrows the space for religious dialog. This research aims to analyze the construction of hate narratives in digital preaching discourse and examine their relationship to the crisis of communication ethics amidst the flow of disinformation. Using a descriptive qualitative approach with Fairclough's Critical Discourse Analysis (CDA) method, this study analyzes the content of religious sermons on the YouTube, X (Twitter), and TikTok platforms that feature hate speech and ideological bias. The research findings indicate that disinformation serves as the primary trigger for the emergence of hate narratives, which then exacerbate the crisis of communication ethics in the digital preaching space. Confrontational da'wah language tends to create a moral dichotomy between